Reliability and Validity of the Student Version of the Oldenburg Burnout Inventory in Physical Therapist Students. Issue 3 (16th September 2022) - Smith, Allison; Ellison, Jennifer; Bogardus, Jennifer; Gleeson, Peggy
Abstract : Introduction: Limited research exists on burnout in physical therapists (PTs) and PT students. The prevalence of PT student burnout is unknown and few outcome measures exist to study burnout in students. The purpose of this study was to assess the test–retest reliability and internal consistency of the Oldenburg Burnout Inventory for Students (OLBI-S) and convergent validity of the OLBI-S with the Maslach Burnout Inventory General Survey for Students (MBI-GSS) in Doctor of Physical Therapy (DPT) students. Review of Literature: Most authors studying burnout have used the MBI, which has been criticized in recent years. The OLBI was developed in response to the criticisms and psychometric limitations of the MBI. The OLBI-S has not yet been validated in PT students. Subjects: Participants included a convenience sample of DPT students attending Texas Woman's University in Houston during the fall semester of 2020. Methods: Students completed the OLBI-S and MBI-GSS and completed the OLBI-S a second time 1 week later. Intraclass correlation coefficients (ICCs) were calculated to examine test–retest reliability, Cronbach's α was calculated to assess internal consistency, and convergent validity was assessed by calculating Pearson's correlations comparing corresponding subscales for the OLBI-S and MBI-GSS. Results: Test–retest reliability was excellent for both the OLBI-S exhaustion subscale (ICC = .916, P < .001) and the OLBI-S disengagement subscale (ICC = .955, P < .001). Internal consistency was good for both the exhaustion subscale (Cronbach's α = .833) and the disengagement subscale (Cronbach's α = .784). Convergent validity was found to be good between the OLBI-S and MBI-GSS exhaustion subscales ( r = .741, P < .001) as well as the disengagement subscale of the OLBI-S and cynicism subscale of the MBI-GSS ( r = .766, P < .001). Discussion and Conclusion: The OLBI-S has excellent reliability, good validity, and is a free alternative outcome measure to the MBI-GSS to measure burnout in DPT students.